Increased degranulation of immune cells is associated with higher cervical viral load in HIV-infected women. (10th September 2018) - Saxena, Vandana; Ghate, Manisha; Bichare, Shubhangi; Khan, Ishrat; Majumdar, Raj; Angadi, Mansa; Kulkarni, Smita; Paranjape, Ramesh; Thakar, Madhuri Rajeev
Abstract : Objective: The activation of effector immune cells at the cervicovaginal mucosa (CVM) might influence the cervical HIV load and thus the secondary transmission; however, limited information is available about the innate effector cells at CVM during HIV infection. In this study, we quantified and assessed the activation of the effector immune cells at the CVM of HIV-infected women with different disease outcomes: nonprogressive HIV disease (LTNPs) and chronic HIV-infected (CHI) and their relationship with cervical viral shedding. Method: The phenotype and frequency of cytobrush-derived effector immune cells like natural killer cells, T cells, and dendritic cells and their degranulation status (CD107a expression as a surrogate marker of activation) was determined using flow cytometry in age-matched HIV- infected and uninfected women and their association with cervical HIV load was determined. Result: The frequencies of dendritic cells, CD56 bright, CD56 dim natural killer cell subsets were similar in both the study groups and also within the HIV-infected women with and without progressive disease. The frequencies of CD56 − CD16 + natural killer cells ( P = 0.04) and degranulating CD56 dim natural killer cells were significantly higher among HIV-infected women ( P < 0.05). Among HIV-infected women, LTNP women showed reduced degranulation of natural killer and CD8 + T cells than seen in the CHI women, which was also associated with lower cervical viral load ( P < 0.05). Conclusion: The present study showed that increased degranulation of natural killer and T cells is associated with higher HIV shedding at the CVM of HIV-infected women. Hence reduction of the local immune activation at CVM could be an effective strategy to reduce the cervical viral load.